The effect of pre-slaughter stressors on physiological indicators and meat quality traits on Merino lambs - Zimerman, María (2013)
Merino lambs of 90 days of mean age (standard deviation - s.d. - 6 days) and 22.0. kg of mean live weight (s.d. 2.7. kg) were used to explore the effects of pre-slaughter stressors on physiological characteristics and meat quality attributes. Three stressors were studied in a controlled experiment: fasting (food deprivation for 24. h before slaughter), physical exercise (keeping animals walking for 30. min at approximately 3. km/h) and fear stress (exposing animals to barking dogs for 5. min). A fourth treatment was kept as a control. Fasted lambs had greater (P<0.05) urea and cortisol concentrations than control. Exercise had no effects (P>0.05) in physiological indicators and lambs exposed to barking dogs had greater (P<0.05) cortisol concentration compared with control. The stressor treatments studied did not affect meat quality parameters. Therefore, even though the stressors imposed on the lambs induced changes in blood constituents typically associated with the stress response, the intensity and (or) duration of these stressors had no effect on meat quality traits.